Komunikasi Persuasif Orang Tua dalam Mencegah Pernikahan Dini pada Remaja di Desa Bandar Klippa - Nadia Auliya (Universitas Muhammadiyah Sumatera Utara, 2026)
This study aims to describe the persuasive communication carried out by parents in preventing early marriage among adolescents in Bandar Klippa Village, Percut Sei Tuan District, Deli Serdang Regency. This research employs a qualitative descriptive method with data collection techniques through interviews, observation, and documentation. The research subjects consisted of two parents as primary informants and two adolescents as supporting informants. The results show that parents consistently apply persuasive communication through repeated advice, enforcement of rules and restrictions in social interactions, and emphasis on the importance of education and readiness before marriage. Parents also use the association technique by presenting real examples from the surrounding environment, the arrangement technique through emotional approaches, and the reward technique by describing the benefits of delaying marriage. The continuous persuasive communication has proven to influence adolescents' perspectives, leading them to prioritize education and the future over early marriage.